Path Analysis of Organizational Climate, Servant Leadership, and Personality on Teachers’ OCB: The Mediating Role of Trust - Nurjanah, Nurjanah; Dasmo, Dasmo; Mailizar, Mailizar; Wati, Septa (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
This study examines the direct and indirect effects of organizational climate, servant leadership, and personality on teachers’ Organizational Citizenship Behavior (OCB), with trust as a mediating variable. Using a quantitative approach, data were collected from 110 private junior high school teachers in Tangerang Regency, Indonesia, and analyzed using regression-based path analysis. The results indicate that organizational climate, servant leadership, personality, and trust each have significant positive direct effects on teachers’ OCB, with trust emerging as the strongest predictor. Further analysis reveals that trust selectively mediates the relationships between servant leadership and OCB, as well as between personality and OCB, while it does not mediate the effect of organizational climate on OCB. These findings suggest that relational and dispositional factors influence teachers’ discretionary behavior primarily through trust-based mechanisms, whereas organizational climate operates through normative or structural pathways. The study contributes to the OCB literature by demonstrating trust as a selective, rather than universal, mediator within an integrated organizational–individual model. Practically, the findings underscore the importance of servant leadership practices and trust-building processes in fostering voluntary and extra-role behavior among teachers.